On optimal stopping for the Markov chain with discounting - Mackevičius, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Мацкявичюс. Об оптимальной остановке марковской цепи с переоценкой V. Mackevičius. Apie Markovo grandinės su perkainojimu optimalų sustabdymų